Adaptive shearing-gradient thickening polishing (AS-GTP) and subsurface damage inhibition. (January 2021) - Li, Min; Karpuschewski, Bernhard; Ohmori, Hitoshi; Riemer, Oltmann; Wang, Ying; Dong, Ting
Abstract: A novel adaptive shearing-gradient thickening polishing (AS-GTP) method is first proposed to improve surface accuracy and restrain subsurface damage on lithium niobite (LiNbO3 or LN) crystal. The material removal rate (MRR) in AS-GTP is established according to adaptive real-shearing flow, temperature-induced gradient thickening (GT) mechanism, and plastic indentation on active GT abrasive concept. The MRR prediction model is verified by the AS-GTP experiments. Results from the theoretical calculation based on the MRR prediction model are closed to that from experimental data, and the maximal difference between the experiment results and theoretical calculation is no greater than 9.5%. The microstructure of the thermosensitive particle (NIPAM-ODA, the copolymer of N-isopropylacrylamide and octadecyl acrylate) has amphiphilic property and results in the gradient thickening for AS-GTPS. Under the conditions of temperature of T 38 °C, average abrasive size of D a 0.6 μm, rotational speed of v r 600 min −1, abrasive concentration of W 12 vol % and gradient-thickening threshold (shear rate 300 s −1 ), surface damage depth ( D d ) and surface roughness ( Ra ) also decline to a minimum critical threshold (<1 nm). The results indicate that the AS-GTP is a promising processing method to achieve subsurface damage inhibition and ultra-smooth surface for LN crystal high-efficiency machining. Graphical abstract: Image 1 Highlights: A novel adaptive shearing-gradient thickening polishing (AS-GTP) method is first proposed for ultraprecision machining. MRR in AS-GTP is modeled according to adaptive real-shearing flow, gradient thickening, and active GT abrasive indentation. The microstructure of thermosensitive particle has amphiphilic property and results in gradient thickening for AS-GTPS. Surface damage depth ( D d ) and roughness ( Ra ) of the polished workpiece decline to a minimum critical threshold (<1 nm). AS-GTP is a promising high-efficiency machining method to achieve subsurface damage inhibition and ultra-smooth surface.